Cryo-EM structures of human STEAP4 reveal mechanism of iron(III) reduction - Wout Oosterheert (Nature Portfolio, 2018)
Enzymes of the six-transmembrane epithelial antigen of the prostate (STEAP) family reduce Fe3+ and Cu2+ ions to facilitate metal-ion uptake by mammalian cells. Here, authors employ single-particle cryo-EM to gain insights into the molecular principles of iron reduction by human STEAP4 .